ANALYSIS OF PRODUCTIVITY AND CHARACTERISTIC SEEDS DAIRY GOATS - G. . Yusupova; D. . Kurmangaliyeva; N. . Lantseva; Zh. . Shadyarova (Алматы технологиялық университетінің хабаршысы, 2021)
The article analyzes the 7 principles of the international standard related to the safety of dairy raw material and its products.Traditionally, the poor quality of milk produced in the country's farmscommonlyoften due to the lack of a system to ensure its quality. Аt the present stage to guarantee the quality is possible through the introduction of a safety management system and product quality based on the standard ST RK ISO (ISO-International Organization for standardization) 22000:2006 "Food safety management systems - Requirements for any organization in the food chain². This system provides control at all stages of food production, at any point in the process of production, storage and sale of products, where there may be dangerous situations and is used mainly by enterprises - producers of food products.